Review of experimental methods to determine spontaneous combustion susceptibility of coal – Indian context - Mohalik, N.K.; Lester, Edward; Lowndes, Ian (Taylor & Francis, 2016)
This paper presents a critical review of the different techniques developed to investigate the susceptibility of coal to spontaneous combustion and fire. These methods may be sub-classified into the two following areas: (1) Basic coal characterisation studies (chemical constituents) and their influence on spontaneous combustion susceptibility. (2) Test methods to assess the susceptibility of a coal sample to spontaneous combustion. This is followed by a critical literature review that summarises previous research with special emphasis given to Indian coals.